Graphene growth from photo-polymerized bi-phenylthiol self-assembled monolayers - Zehra, Tashfeen; Syari’ati, Ali; Ivashenko, Oleksii; Bignardi, Luca; Van Dorp, Willem F.; De Hosson, Jeff T. M.; Rudolf, Petra (Frontiers in Nanotechnology, 2024)
We present an enhanced methodology for the synthesis of graphene utilizing photo-polymerized selfassembled monolayers (SAMs) of 1,1ʹ-biphenyl-4-thiol on both electropolished and oxidized copper substrates. The SAMs underwent a two-step process involving light-induced polymerization followed by annealing in a vacuum furnace to yield the two-dimensional solid. Comprehensive characterization using contact angle measurements, X-ray photoelectron spectroscopy, Raman spectroscopy, as well as scanning electron and transmission electron microscopy, provided conclusive evidence of single-layer graphene growth. Notably, our findings revealed superior quality graphene on oxidized copper substrates compared to electropolished counterparts, highlighting the impact of substrate choice on the resultant material quality.